On the linguistic training of future teachers of unlike specialties under the conditions of Russian professional education - Igorevna Vaganova, Olga; N. Zanfir, Ludmila; Venediktovna Smirnova, Zhanna; Aleksandrovna Chelnokova, Elena; Nikolaevna Kaznacheeva, Svetlana; Maseleno, Andino (International Journal of Engineering and Technology, 2018)
In the modern world much attention is paid to foreign-language preparation of students, since this is an important component of the graduate's professionalism. In Russia today only high-quality higher education institutions provide quality linguistic training. Therefore, it is necessary to pay attention to non-linguistic higher schools. The aim of the work was to improve the quality of the linguistic training of future teachers. To achieve the goal, we set ourselves the tasks: to determine the significance, content and characteristics of the formation of linguistic training; to analyze the state of professional linguistic training in a modern higher school; to determine and substantiate the content that contributes to the successful formation of a communicative competence that is foreign-speaking - a future graduate. In the work we conducted a study to check the level of the formation of linguistic culture. Participation in the experiment was accepted by students of Minin Nizhny Novgorod State Pedagogical University. The stages of foreign language training with a target setting, the final and intermediate goals of teaching a foreign language at the university are determined. We also considered the formation of the communicative competence of the second-year students who speak foreign languages. The results of the research showed a sufficient level of development of this competence but the university continues to improve the preparation of students in this field.Â Â
Keywords: Linguistic Training; Linguistic Culture; Non-Linguistic Specialties; Vocational-Oriented Training; Competences; Higher School.